GILZ as a Mediator of the Anti-Inflammatory Effects of Glucocorticoids - Ronchetti, Simona; Migliorati, Graziella; Riccardi, Carlo (Frontiers in Endocrinology, 2015)
Glucocorticoid-induced leucine zipper (GILZ) is a dexamethasone-inducible gene that mediates glucocorticoid (GC) actions in a variety of cell types, including many cells of immune system. In particular, GILZ can control T cell activities, such as activation and differentiation, mainly through its ability to homo- and hetero-dimerize with partner proteins, such as NF-κB, Ras, and C/EBP. These protein–protein interactions control the regulation of pro-inflammatory target genes. A number of in vitro and in vivo studies using mouse models of inflammatory diseases demonstrate an anti-inflammatory role for GILZ. Here, authors summarize the studies that make GILZ eligible as an anti-inflammatory protein through which GCs can act. These findings permit the future development of pharmacological tools that mimic the therapeutic effects of GCs while avoiding the detrimental ones.